Global Warming and changes in sea ice in the Greenland sea: 1979 - 2007 - Maxine von Eye (University of Cambridge); Alexander Von Eye (University of Vienna); Joao Rodrigues (University of Cambridge) (2009)
The abstract is available here: https://uscholar.univie.ac.at/o:244883 The abstract is available here: https://uscholar.univie.ac.at/o:244883